Preoperative risk factors for complications in esophagectomy: a systematic review - Ramchandani, Rashi; Jaremek, Adam; Rathod, Jharna; Lee, Alex; Guo, Eddie; Rakab, Esra; Dhawan, Alaina; Munro, Cole; Hurley, Kate; Lisondra, James; Dhawan, Jillian; Khan, Zaim; et al. (Current Challenges in Thoracic Surgery; Vol 8 (June 30, 2026): Current Challenges in Thoracic Surgery, 2026)
Background: Early identification of patients at increased risk of postoperative complications following esophagectomy is critical for targeted optimization. The objective is to systematically review preoperative risk factors associated with 30-day postoperative complications after esophagectomy for malignancy.Methods: A comprehensive search of MEDLINE, Embase, and Web of Science was performed from inception to July 2025 following PRISMA guidelines. Studies evaluating preoperative patient, tumor, and treatment-related factors in relation to common 30-day complications were included. Inclusion criteria included studies involving human adults, published in English that reported associations between preoperative risk factors and 30-day postoperative complications. Odds ratios (ORs) and 95% confidence intervals (CIs) were extracted where available by two independent reviewers. Risk of bias was assessed using a modified Risk-of-Bias in Non-randomized Studies of Interventions (ROBINS-I) framework, and results were summarized descriptively due to heterogeneity.Results: Across the 96 included studies, higher American Society of Anesthesiologists (ASA) score (≥ III), age >65 years, and body mass index (BMI) extremes were consistently associated with increased 30-day mortality and cardiorespiratory complications. Sarcopenia was linked to a higher risk of pneumonia, while elevated aspartate aminotransferase (AST) predicted increased short-term mortality. Overweight patients (BMI: 25–29.9 kg/m2) had greater odds of pneumonia and wound infection, and obesity (BMI >30 kg/m2) was associated with mortality. Other commonly reported preoperative risk factors included vascular (peripheral or coronary) calcification, preoperative radiation exposure, and lymph node positivity. Smoking did not consistently correlate with increased 30-day postoperative complications.Conclusions: This review confirms established predictors and highlights emerging preoperative risk factors that warrant further investigation. These findings support targeted perioperative optimization, including nutritional support, respiratory conditioning, and vascular assessment, to improve early outcomes after esophagectomy.